Evidence of Lactobacillus reuteri to reduce colic in breastfed babies: Systematic review and meta-analysis - Angela Pierina dos Reis Buzzo Zermiani; Ana Luiza Pelissari Peçanha de Paula Soares; Bárbara Leticia da Silva Guedes de Moura; Edson Roberto Arpini Miguel; Luciana Dias Ghiraldi Lopes; Natália de Carvalho Scharf Santana; Thais da Silva Santos; Izabel Galhardo Demarchi; Jorge Juarez Teixeira (Elsevier, 2021)
Objective: To investigate evidence for the treatment of childhood colic by supplementing Lactobacillus reuteri in infants breastfed with breast milk. Methods: The study was conducted according to the PRISMA protocol. The databases used for acquiring data were PubMed and Web of Science, applying MeSH terms and free terms. Meta-analysis was conducted using Stata ™ 12.0. The risk of bias was evaluated by the Review Manager (RevMan) 5.3 tool, and the strength of evidence was assessed by the Grading of Recommendations Assessment, Development and Evaluation (GRADE). Results: Ten clinical trials were included in the review. The administration of L. reuteri (DSM 17938 or ATCC55730) was tested in infants (n = 248) versus the control/placebo group (n = 229). Eight articles were included in the meta-analysis. There was a significant response in reducing crying time (minutes/day) and treatment effectiveness (reduction ≥ 50% in average daily crying time) in the first week (p = 0.001 and p = 0.003, respectively). These results were similar in the second, third weeks (p < 0.001 for both outcomes) and fourth weeks (p<0.001 and p = 0.002, respectively). The risk of bias was low for the majority of the studies. Confidence in evidence was considered very low for crying time and low for effectiveness treatment. Conclusions: The evidence shows that the administration of Lactobacillus reuteri to babies fed with breast milk reduces the crying time in babies diagnosed with colic. But our confidence in the effect estimate is limited.